Glasgow and Shanghai Cities as Learning Cities for Continuous Education: What Impact On Society as a Whole? - Sherwan T. Ameen (European Scientific Journal, ESJ, 2020)
Continuous education is focussed via the concerns of globalization, prompt transformation and the requirement aimed at public presence, national, regional and resident governments are altering their interpretation of education. That is why learning becomes the ambitions of governments to create cities of learning to reach the ultimate development in all sectors. In a continuously growing and complex world, the major cities are competing to become cities of learning, helping their citizens from all social levels and backgrounds. Construction a learning culture and brand lifelong learning an authenticity, it is significant to boost and attach entirely learning categories. Hence, learning is fundamental to attainment and prosperity, for individuals, families, communities, and nations worldwide. The key role of learning cities is to develop equality and economic stability, prosperity, personal fulfilment and mobilizes all their humans to reach full human potential. There are some key features and measurements of learning cities and challenges for each city to face for them to be considered as a learning city. Enabling citizens the opportunity to become literate is one of the most significant measures of the learning city. It should also encourage its citizens to be motivated to the building of their city. This paper focuses and assesses the examples of two cities from two different continents, namely Glasgow in the UK, Shanghai in China to evaluate the key features and different dimensions of these cities which are attempting to reach learning city status. Finally shaping some scopes for the policymakers and researchers around the world uncover the responses in continuing research to stretch the goals and critical features of learning cities. Personally the ideas of learning cities is a vital towardsthe supreme aim of education and more closely the lifelong learning as a whole package.